Effect of Malaria and Schistosoma mansoni Coinfection on Selected Biochemical Profiles among Patients Attending Selected Health Institutions at Dembiya, Northwest Ethiopia - Wagaw Abebe; Wossenseged Lemma; Yalewayker Tegegne; Amare Mekuanint; Abebe Yenesew; Adane Derso (Journal of Tropical Medicine)
Background. Malaria and schistosomiasis are infectious diseases that cause biochemical abnormalities. Malaria and Schistosoma mansoni coinfection causes exacerbations of health consequences and comorbidities. The study area is found in Ethiopia, where coinfection of malaria and S. mansoni is common. However, there is limited data on the biochemical profiles of patients coinfected with malaria and S. mansoni schistosomiasis in the study area. Hence, this study aimed to assess the effect of malaria and S. mansoni schistosomiasis coinfection on selected biochemical profiles. Methods. An institutional-based comparative cross-sectional study was conducted from March 30 to August 10, 2022. Using a convenient sampling technique, 70 participants (35 cases and 35 controls) were enrolled in the study. Schistosoma mansoni was detected in stool samples using the wet mount and the Kato Katz method. To detect Plasmodium, both thick and thin blood films were prepared and stained with Giemsa. The blood sample was processed for the analysis of biochemical profiles. All data were analyzed using SPSS version 25. A p value of less than 0.05 was considered statistically significant. Results. The mean values of alanine aminotransferase and aspartate aminotransferase (37.1 U/L and 41.9 U/L, respectively) in coinfected participants were significantly higher than in the healthy control participants (17.4 U/L and 22.0 U/L, respectively) p<0.05. Also, the median values of creatinine, total bilirubin, and direct bilirubin (1.51 mg/dL, 2.35 mg/dL, and 0.91 mg/dL, respectively) in coinfected participants were significantly higher than in the healthy control participants (0.85 mg/dL, 0.42 mg/dL, and 0.12 mg/dL, respectively) p<0.05. However, median values of total protein (4.82 g/dL) and mean values of glucose (66.6 mg/dL) in coinfected participants were significantly lower than in the healthy control participants (total protein (7.64 g/dL) and glucose (91.9 mg/dL)) p<0.05. The results of biochemical profiles in healthy participants were significantly different from those with light, moderate, and heavy S. mansoni infection intensity in malaria and S. mansoni coinfection p<0.05. Schistosoma mansoni infection intensity had a positive correlation with biochemical profiles except for total protein and glucose, which correlated negatively in coinfected participants p>0.05. Conclusion. Biochemical profiles in coinfection were significantly changed as compared to healthy individuals. As a result, biochemical profile tests should be utilized to monitor and manage coinfection-related problems, as well as to reduce coinfection-related morbidity and death.